PERLINDUNGAN HUKUM TERHADAP REKAM MEDIS PASIEN DI RUMAH SAKIT - Mariani, Made Dwi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 2 (2015)DO - 10.24843/JMHU.2015.v04.i02.p18, 2015)
Patient as consumers of health service have rights one of the rights is the state of the patients health is being concealed forever including medical data and medical records. Regarding to that, hospital as the health care provider obliged to provide legal protection to all kind of information in the medical record to the possibility of loss of information, data falsification or used by the undue. Based on that, the problem to be studied is: how is the medical record management in the hospital? And how is the medical record legal protection,  which is given by the hospital? This study use normative legal research with statue approach. All of the legal resources based on library research and supported by primary and secondary legal material. Legal research analysis technique in this study use descriptive technique. The study result showed that the medical record management in the hospital have to based on health minister regulation 269/MENKES/PER/III/2008 about medical records. The management of medical record started from the time patient came to the hospital with record all action that given to the patient until all the treatment completed. The data and information on the medical record, hospital has an obligation of giving legal protection about the confidentiality based on Articles 10 health minister regulation 269/MENKES/PER/III/2008 with form of preventive and repressive protection.
Keywords: Medical Record, legal protection, hospital